2021
DOI: 10.1021/acsmacrolett.1c00319
|View full text |Cite
|
Sign up to set email alerts
|

Two Sides of the Same Coin: Light as a Tool to Control and Map Microsphere Design

Abstract: Herein, we establish the effect of intensity and wavelength on the size of microparticles formed via precipitation polymerization, employing photocrosslinkable prepolymers. Simultaneous measurement of backscattered laser irradiation enabled real-time tracking of particle growth and provides the ability to vary the LED intensity (λ max = 415 nm) during various stages of particle growth. Critically, particle diameters can be controlled between 200 and 700 nm by varying the LED power from 73 to 0.63 mW, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…A 10 W LED was also employed and the experiments produced larger particles ( D n = 1.06 μm) with a very low dispersity ( Ð = 1.03, run 1.1_B). Our team recently developed a methodology to track the early stages of polymer particle nucleation and growth by employing the backscattering of a laser irradiation 30 . The real-time tracking of particle growth was compared to the final particles size measured by SEM and we observed that the LED power as well as the wavelength govern the final particle diameter.…”
Section: Resultsmentioning
confidence: 99%
“…A 10 W LED was also employed and the experiments produced larger particles ( D n = 1.06 μm) with a very low dispersity ( Ð = 1.03, run 1.1_B). Our team recently developed a methodology to track the early stages of polymer particle nucleation and growth by employing the backscattering of a laser irradiation 30 . The real-time tracking of particle growth was compared to the final particles size measured by SEM and we observed that the LED power as well as the wavelength govern the final particle diameter.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, thermoresponsive microgels can be facilely prepared by in situ cross-linking of prepolymer droplets or aggregates through emulsification, microfluidics, or self-assembly methods. , For example, thermally induced aggregates from linear poly­( N -isopropylacrylamide) derivatives or oligo­(ethylene glycol)-modified polymers were in situ cross-linked into microgels in aqueous solutions through dynamic covalent bonds. Similarly, temperature-induced self-assembly and subsequent self-cross-linking of disulfide-contained hyperbranched polymers afforded bioreducible microgels without the need of any stabilizer or additional cross-linking agents . Recently, photocycloaddition chemistry has been employed as a clean, robust, and spatiotemporally controlled tool to mediate cross-linking of polymers. The precursor polymers appended with photoactive chromophores such as cinnamate and cumarin can be efficiently cross-linked into microgels by UV irradiation. ,, Shell-cross-linked hollow particles or microgels were also facilely prepared by controlling selective photocycloaddition at the interfaces of spherical polymer particles followed by removal of the non-cross-linked polymer in the core region. In some cases, visible light-induced cross-linking of prepolymers was exploited to produce precisely controlled fluorescent microspheres without the use of any additives such as initiators, surfactants, or cross-linking agents. These new progress demonstrated the significant advantages of photocycloaddition techniques for efficient fabrication of functional microgels.…”
Section: Introductionmentioning
confidence: 99%